EXPENSE AND LOSSES OF PETROLEUM, OIL AND LUBRICANTS FOR MOBILE AGRICULTURAL MACHINERY - Z. A. Godzhaev; Yu. N. Sapyan; V. A. Kolos; M. I. Gorshkov (Сельскохозяйственные машины и технологии, 2017)
The machine and tractor fleet (MTF) quality in farms is characterized by its of physical and moral aging. If a number of traktors in the fleet with the limit-exceeding service life is more than 60 percent, then the carrying costs for the equipment in good operating condition increases 1.8 times, the petroleum, oils and lubricants (POL) consumption rises 1.5 times. Processes of fleet aging were followed by its reduction from 1365.6 thousand units in 1990 till 259.7 thousand tractors in 2013. The authors analyzed data on farms economy and production in Rostov region. The results of tests of mobile machines were carried out at the he North Caucasian test station under conditions of ordinary operation. The authors studied a MTF grade composition, identified main POL consumers, expenditure level, causes of non-production outlay. Tractors of the Minsk tractor plant make 35.6-37.3 percent that means the largest proportion in the structure of MTF in the surveyed farms. Oil filling-up in the engine reaches to 86 percent in the average total oil consumption by the engines of tractors. This fact indicates heavy physical wear of the cylinder-piston groups in the motor-and-tractor diesels. The amount of unproductive consumption and POL loss at machines operation depend on seal leakiness, the low quality of the production of parts, components, and assemblies of hydraulic systems.